2006
DOI: 10.1002/pssc.200669569
|View full text |Cite
|
Sign up to set email alerts
|

Optical constants at and below energy gap of layered ternary Tl compounds

Abstract: Incoherent reflection mode of spectroscopic phase modulated ellipsometry (SPME) was firstly applied to quasi-two-dimensional TlInS 2 , TlGaS 2 and TlGaSe 2 to obtain uniaxial optical anisotropy of these materials at room temperature. Simulation of the measured SPME signal was performed within uniaxial incoherent reflection model, with a result of perfect match to experimental data for all three compounds. Birefringence in a photon energy range from below the energy gap of each material and down to 0.76eV was r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…In our works [6,7] the accurate values of the refractive index of TlInS 2 were obtained in both orientations, E//C* and E⊥C*(C*: direction normal to the layer plane, E: electrical vector) at room temperature in a range of the photon energies below the energy gap by using spectroscopic ellipsometry and so-called incoherent reflection model [8].…”
mentioning
confidence: 99%
“…In our works [6,7] the accurate values of the refractive index of TlInS 2 were obtained in both orientations, E//C* and E⊥C*(C*: direction normal to the layer plane, E: electrical vector) at room temperature in a range of the photon energies below the energy gap by using spectroscopic ellipsometry and so-called incoherent reflection model [8].…”
mentioning
confidence: 99%
“…6 we demonstrate the obtained photon energy dependence of the birefringence for all TlMeX 2 . More details about refractive indices of TlMeX 2 can be found in the work [28]. Here we would like only to mention that fast SPME is an ideal optical technique to study the photo-refraction and its time development in a relaxor state of layered TlMeX 2 [18], as well as to get information on Burns temperature [29] for glassy state of these materials by measuring the effect of residual spontaneous polarization on refractive indices due to quadratic electro-optic effect.…”
Section: Spme In Incoherent Reflection Modementioning
confidence: 99%
“…[3][4][5][6][7][8][9][10] It was revealed that the fundamental absorption edge is formed by indirect transitions with band gap energies E gi ¼ 1.98 and 2.06 eV (TlGaSe 2 ) and E gi ¼ 2.27 and 2.44 eV (TlInS 2 ) at T ¼ 300 and 10 K, respectively. 11,12 A high photosensitivity in the visible range, high birefringence in conjunction with a wide transparency range of 0.6-16 lm make these crystals useful for optoelectronic applications.…”
Section: Introductionmentioning
confidence: 99%